Essence and Conceptual Foundations of The Concept of Information Security - Muratovich, Mamadjanov Alisher (Indonesian Journal Publisher, 2020)
This article examines the essence and conceptual foundations of the concept of information security. The influence of information threats and attacks on the development and formation of youth